Department of Sports and Leisure of the Municipality of Valinhos - SP: Legal Framework for the Promotion of Public Policies - Giolo-Melo, Caroline; Pacheco, Reinaldo Tadeu Boscolo (Brazilian Journal of Science, 2022)
The practice of physical activity provides benefits to physical and mental health. Public policies of sport and leisure are essential to guarantee the access of the general population to oriented physical exercise programs and to places that allow autonomous practice. In this perspective, the present study refers to a documentary research, with a qualitative approach, carried out at the end of the second semester of 2016 and beginning of the first semester of 2017, in internal records of the Sports and Leisure Department of the city of Valinhos - SP, official website of the City Hall and City Council, Municipal Laws, Official Press (Municipal Bulletin), minutes of the Municipal Sports Council and information provided by the Sports Directors. This is the documentary part of the research that originated the master's dissertation entitled "Public policy and quality of life: a study about the gymnastics groups of the City Hall of Valinhos - SP", presented to the University of São Paulo - USP, in 2019. Thus, in this article, the Laws related to the functioning of the activities of the Sports and Leisure Department will be exposed, which guarantee the provision of public policies for Sports and leisure in the municipality. The following will be presented: Multi-Year Plan, for the period from 2014 to 2017, (Municipal Law nº 4,957 of December 13th, 2013), Budget Guidelines Law (Municipal Law nº 5,314 of July 18th, 2016), Annual Budget Law for the year 2017 (Municipal Law nº 5,373 of December 14th, 2016), the Municipal Sports Council and the Municipal Sports Fund of Valinhos (Municipal Law nº 4,759 of May 23th, 2012). Also the relationship between the work carried out in the Secretariat with the guidelines of the Municipal Master Plan (Municipal Law nº 3,841 of December 21st, 2004) and Municipal Organic Law (enacted on April 5th, 1990). This article also aims to serve as a basis for future research in the area, as well as for the elaboration of new policies, emphasizing that these must be inclusive, democratic and decentralized, as well as periodically evaluated.